The Poems of Emma Lazarus, Volume 2 : Jewish poems: Translations - Lazarus, Emma, 1849-1887 (Salt Lake City, UT : Project Gutenberg, 2002)
"The Poems of Emma Lazarus, Volume 2" by Emma Lazarus is a collection of poetry that was likely written during the late 19th century. This volume particularly showcases Jewish themes and translations of Hebrew works, reflecting the deep cultural and historical resonance of Jewish identity. The book serves as a poignant exploration of themes such as suffering, identity, resilience, and hope within the Jewish experience, presenting a spiritual and artistic homage to Lazarus's heritage. The opening of this volume begins with a biographical sketch of Emma Lazarus, offering insight into her life and the artistic influences that shaped her poetic voice. It highlights her early experiences with grief and nostalgia, revealing how these emotions evolved into a mature expression of Jewish identity and cultural pride. In the initial poems, themes of exile, historical legacy, and the Jewish New Year are explored, alluding to the somber yet hopeful journey of the Jewish people through history. The essence of her work resonates with a yearning for homeland and identity, coupled with a passionate call for unity and remembrance among her people. This emphasis on the intersection of personal and collective memory sets the tone for the rest of her compelling collection. (This is an automatically generated summary.)
Release date is 2002-10-01
Produced by Douglas E. Levy, and David Widger
Keywords: American poetry; Literature -- Collections